STUDENT EMPOWERMENT IN MOBILE-ASSISTED ENGLISH LANGUAGE LEARNING FOR LISTENING SKILL - Risalatul Hanifah Hasibuan; Bambang Widi Pratolo (PROJECT (Professional Journal of English Education), 2024)
Mobile-Assisted Language Learning (MALL) has become an increasingly important component of teaching and learning in university environments, especially in the context of listening classes and interpreting audio in foreign languages. This study used mixed qualitative and quantitative research methods, including surveys and interviews, to collect data about the use of MALL in listening classes in university settings. The results of this study describe students' perceptions, and voices, and identify the challenges students face when participating in Mobile-Assisted English Learning for listening activities. In the context of a listening class, MALL allows students to practice listening with a diversity of audio sources, including recorded speeches, interviews, and other structured audio materials. This ability can improve their oral comprehension skills and expand their understanding of language variations used in real situations. This research concludes that MALL can be an effective tool for improving students' listening skills in a university environment.